2010
DOI: 10.1016/j.pbb.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of ambroxol in rats with neuropathic spinal cord injury pain

Abstract: Symptoms of neuropathic spinal cord injury (SCI) pain include evoked cutaneous hypersensitivity and spontaneous pain, which can be present below the level of the injury. Adverse side-effects obtained with currently available analgesics complicate effective pain management in SCI patients. Voltage-gated Na + channels expressed in primary afferent nociceptors have been identified to mediate persistent hyperexcitability in dorsal root ganglia (DRG) neurons, which in part underlies the symptoms of nerve injury-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 51 publications
3
31
0
3
Order By: Relevance
“…Dies könnte der Grund dafür sein, dass 4 unserer Patienten ohne vorherige Lidocainwirkung dennoch von Ambroxol profitierten. Ambroxol war auch nach systemischer Gabe in Tiermodellen des neuropathischen Schmerzes hochpotent wirksam [14,16], mindestens so stark wie Gabapentin und in Dosierungen, die durchaus klinisch eingesetzt werden können [14,49]. Na v in Nervenzellmembranen spielen eine wichtige Rolle für die Signaltransduktion, u. a. auch in nozizeptiven Neuronen.…”
Section: Pharmakologie Natriumkanäle Und Analgetische Wirkungenunclassified
See 2 more Smart Citations
“…Dies könnte der Grund dafür sein, dass 4 unserer Patienten ohne vorherige Lidocainwirkung dennoch von Ambroxol profitierten. Ambroxol war auch nach systemischer Gabe in Tiermodellen des neuropathischen Schmerzes hochpotent wirksam [14,16], mindestens so stark wie Gabapentin und in Dosierungen, die durchaus klinisch eingesetzt werden können [14,49]. Na v in Nervenzellmembranen spielen eine wichtige Rolle für die Signaltransduktion, u. a. auch in nozizeptiven Neuronen.…”
Section: Pharmakologie Natriumkanäle Und Analgetische Wirkungenunclassified
“…Schon früh wurden lokalanästhetische Eigenschaften erkannt [23], weshalb ambroxolhaltige Lutschpastillen auch zur Behandlung von Halsschmerzen zugelassen sind [10]. Ein anderer Einsatz als Analgetikum erfolgte allerdings bisher nie, obwohl im Tiermodell schmerzbedingte Verhaltensweisen auch bei chronischem Schmerz unterdrückt werden [14,16,27,32].Ambroxol ist im Vergleich zu anderen Lokalanästhetika interessanterweise ein ausgesprochen potenter Blocker spannungsabhängiger Natriumkanäle (Na v ). Es hemmt Natriumkanäle mit etwa 40-fach höherer Potenz als Lidocain [47].…”
unclassified
See 1 more Smart Citation
“…VGSCs are predominantly distributed in small-diameter DRG neurons that mediate nociceptive transmission via primary Aδ-and C-fibers. We know that DRG neurons contribute to below-level neuropathic pain after rodent SCI because some articles report that systemic, not intrathecal, administration of sodium-channel blockers, such as ambroxol and mexiletine, attenuated mechanical allodynia and thermal hyperalgesia in rat hind paws [12,13].…”
Section: Peripheral Sensitization After Spinal Cord Injurymentioning
confidence: 99%
“…Further, tricyclic anti-depressants (i.e., amitriptyline, nortriptyline and imipramine) and anti-convulsants (i.e., phenytoin, carbamazepine, gabapentin, lamotrigine and topiramate) have also been reported to produce antiallodynic effects in neuropathy (Lee et al, 2000;Dwight, 2006). However, these drugs are reported to exhibit a wide spectrum of adverse effects which limit their full clinical exploitation in management of painful neuropathy (Carol & Jane 2006;Hama et al, 2010). Moreover, none of the medications assessed in randomized controlled studies conducted has been found effective in Complex Regional Pain Syndrome i.e.…”
Section: Introductionmentioning
confidence: 99%